2017
DOI: 10.1111/jop.12668
|View full text |Cite
|
Sign up to set email alerts
|

STRO‐1 confers myofibroblast transdifferentiation in fibroblasts derived from oral submucous fibrosis

Abstract: These findings suggested that the stemness marker STRO-1 may be a crucial factor in the pathogenesis of areca quid chewing-associated OSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…116 The increased conversion of fibroblasts into myofibroblasts and upregulated stemness are indicated by their increased contraction, migration, invasion and expression of α-SMA and the pro α-1 chain of type-1 collagen. 116 These MSCs can serve as a source of multipotent cells that can rapidly repopulate the wound in response to epithelial injury. 116 Ye et al 117 showed that growth-regulated oncogene-α (GRO-α) secretion by OSF fibroblasts promotes oral keratinocyte malignant transformation by augmenting EGFR/ERK signalling, F-actin rearrangement and stemness.…”
Section: Rise Of Cancer Stem Cells-dichotomy Of Areca Nut Ingredientsmentioning
confidence: 99%
See 3 more Smart Citations
“…116 The increased conversion of fibroblasts into myofibroblasts and upregulated stemness are indicated by their increased contraction, migration, invasion and expression of α-SMA and the pro α-1 chain of type-1 collagen. 116 These MSCs can serve as a source of multipotent cells that can rapidly repopulate the wound in response to epithelial injury. 116 Ye et al 117 showed that growth-regulated oncogene-α (GRO-α) secretion by OSF fibroblasts promotes oral keratinocyte malignant transformation by augmenting EGFR/ERK signalling, F-actin rearrangement and stemness.…”
Section: Rise Of Cancer Stem Cells-dichotomy Of Areca Nut Ingredientsmentioning
confidence: 99%
“…116 These MSCs can serve as a source of multipotent cells that can rapidly repopulate the wound in response to epithelial injury. 116 Ye et al 117 showed that growth-regulated oncogene-α (GRO-α) secretion by OSF fibroblasts promotes oral keratinocyte malignant transformation by augmenting EGFR/ERK signalling, F-actin rearrangement and stemness. Transformed keratinocytes can then acquire further genetic alterations with the evolution of more invasive clones.…”
Section: Rise Of Cancer Stem Cells-dichotomy Of Areca Nut Ingredientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the aetiology has not been well‐understood, the implication of areca nut chewing was observed in the development of OSF . A number of studies have demonstrated that areca nut upregulated various epithelial‐mesenchymal transition (EMT) and stemness factors, which may lead to myofibroblast transdifferentiation from human buccal mucosal fibroblasts (BMFs). It has been known that persistent activation of myofibroblasts resulted in excessive deposition of extracellular matrix (ECM), leading to pathological fibrosis.…”
Section: Introductionmentioning
confidence: 99%